Inovasi Teknologi 4.0 terhadap Pembelajaran Akuntansi SMA N 1 Banyudono - Damayanti, Desinta Irma; Asmawan, Moh. Chairil (Owner : Riset dan Jurnal Akuntansi, 2024)
The development of technology 4.0 has had a major influence on the world of education. Like SMAN 1 Banyudono, where accounting learning used to only use the lecture method so it did not foster enthusiasm for learning. So technological innovation 4.0 is needed in accounting learning. This research aims to determine technological innovation 4.0 in accounting learning and obstacles and implementation solutions. This research is case study research with a qualitative approach. The object of this research is SMAN 1 Banyudono. The research subjects consisted of: deputy principal, accounting teacher, and students. Data collection techniques using interviews and documentation. This research uses data validity techniques of source triangulation and member check. Data analysis went through three stages, namely data reduction, data presentation and drawing conclusions. The research results show that technological innovation 4.0 in accounting learning in class XI IPS was carried out using computers, whatsapp group, e-school, zoom, Zahir accounting, and Google Classroom. Barriers: not all teachers and students have the same ability to use technology in accounting learning. Instability of the Wi-Fi network in schools slows down the learning process and creates an unconducive classroom atmosphere, uses more internet quota, not all students have laptops, differences in the memory capacity of students' cellphones are not the same so not all students can download learning applications. Solution: provide material and questions in the form of print outs, improve and expand Wi-Fi networks, add computers, and provide quota assistance to underprivileged students.